The Dialectic of Humanization "Belonging" and Bestialization "Non-belonging" in Lamiyat al-Arab: A Comparative and Analytical Approach - Al Kaabi, Mozah H. (Journal of Ecohumanism, 2025)
The study sought to justify and explain contradictions in Al-Shanfara’s Lamiyyah between the poet’s rejection of society versus isolation and wilderness survival. It attempts a fresh textual reading, postponing historical preconceptions about vagabonds (Sa’alik). The study examines the poem’s dialectical approach between savagery and humanity, explores the reasons behind this debate, and whether conflicts between belonging/non-belonging indicate the poet’s truthfulness or deception. The study examines the highly significant Lamiyyah poem, translated into multiple languages, using psychological analysis focusing on artistic appreciation psychology. Poetry reflects the poet’s psychology - writers express repressed desires through literary characters. Art’s value lies in allowing audiences to experience catharsis through fulfilled repressed desires. For vagabond poets, isolation enables desire fulfillment. The analysis reveals the poem’s dialectical approach between conflicting beliefs and explores the reasons behind these contradictions. The study’s importance stems from responding to orientalists who criticize Arab literature as fake, satirical, and authority-driven (Barrunah, 2008, p.65). The poet’s apparent rebellion versus inner adherence to the community stems from a high ego. The natural sense of belonging and need for community is present in the poet’s subconscious. Arab text study, especially deviant poetic phenomena, requires excluding preset narratives and focusing on poetic structure for fresh critical perspectives unbound by traditional accounts. The findings of the study under consideration concern the shifting relationship between the human and the savage in Al-Shanfara’s Lamiyyah and stress the poet’s psychological struggle between acceptance of the tribal society and rejection of its values. The reading and interpretation show that what Al-Shanfara presents as empowering on the surface – isolation, and independence – is a semiotic and rhetorical desire for belonging. The study also compares the work of Al-Shanfara with the other vagabond poet, Urwa ibn Al-Ward, to find that while both poets are rebellious against tribal structures, Urwa still has a morality of belonging and collective responsibility. At the same time, Al-Shanfara rejects this entirely in favor of his desire to be a lone drifter. Thus, these results help to enhance the knowledge of the psychological motivations and the cultural settings of vagabond poetry and its relative tension between individualism and conformism.